Pharmacokinetics of Saruplase, a Recombinant Unglycosylated Human Single-Chain Urokinase-Type Plasminogen Activator and Its Effects on Fibrinolytic and Haemostatic Parameters in Healthy Male Subjects - de Boer, A; Kluft, C; Gerloff, J; Dooijewaard, G; Günzler, W A; Beier, H; van der Meer, F J M; Cohen, A F (Thrombosis and Haemostasis, 1993)
Pharmacokinetics of two doses of the recombinant single-chain urokinase-type plasminogen activator (r-scu-PA) saruplase (40 and 20 mg) and its effect on fibrinolytic and haemostatic parameters were studied in six healthy male subjects using a randomized, double-blind, placebo-controlled, cross-over study. Special precautions were taken to prevent artefactual in vitro effects on fibrinolytic activity.The clearance of saruplase ranged from 310 to 862 ml/min and the apparent volume of distribution of the central compartment was about 8 1. Both doses of saruplase caused α2-antiplasmin consumption, indicating some systemic fibrinolytic activation. However, the 20 mg dose caused no detectable fibrinogen breakdown and only a small increase in total fibrin/fibrinogen degradation products (TDP) (from 0.16 μg/ml [range 0.14 to 0.19] to 0.78 μg/ml [range 0.56 to 1.26]), while the 40 mg dose produce a fibrinogen breakdown to an average value of 44% (range 19 to 60%) and TDP increased from 0.12 μg/ml (range 0.11–0.12) to 2.29 μg/ml (range 0.45 to 5.55). The breakdown of fibrinogen was related to the quantity of saruplase converted to active two-chain u-PA (tcu-PA) in vivo (6 to 22% conversion). There were no important effects of saruplase on overall blood coagulation (activated partial thromboplastin time) and platelet function (collagen induced platelet aggregation, urinary [2,3-dinor]-thromboxane B2 excretion and plasminogen activator inhibitor 1 [PAI-1] release from platelets).Saruplase is cleared rapidly from the plasma and a variable amount is converted to tcu-PA. This two-chain form of u-PA probably causes the dose-dependent systemic fibrinolytic activation.